2018
DOI: 10.3390/w10010083
|View full text |Cite
|
Sign up to set email alerts
|

Using a Backpropagation Artificial Neural Network to Predict Nutrient Removal in Tidal Flow Constructed Wetlands

Abstract: Nutrient removal in tidal flow constructed wetlands (TF-CW) is a complex series of nonlinear multi-parameter interactions. We simulated three tidal flow systems and a continuous vertical flow system filled with synthetic wastewater and compared the influent and effluent concentrations to examine (1) nutrient removal in artificial TF-CWs, and (2) the ability of a backpropagation (BP) artificial neural network to predict nutrient removal. The nutrient removal rates were higher under tidal flow when the idle/reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Wetlands are useful for controlling pollution related to phosphorus (P) [1][2][3][4], as it may be taken up by vegetation before being washed into lakes or rivers. Much research is concerned with the effects of P removal by plants in wetlands [1,5,6], especially with the control of non-point source pollution [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands are useful for controlling pollution related to phosphorus (P) [1][2][3][4], as it may be taken up by vegetation before being washed into lakes or rivers. Much research is concerned with the effects of P removal by plants in wetlands [1,5,6], especially with the control of non-point source pollution [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ramya J. et al [31] and Wei L. et al [32] have designed and gave a simulation system as illustrated in Figure 15 and Figure 16 respectively, which they shown that the best value of MSE equal to 4.3515e-14 and equal to 1.3205e-15 were reached at the epoch 24 and 36 respectively. Thus, from the other previous works, we conclude that our proposed BPNN gets the best results in the training testing performance value, where the best SME value was equal to 1.85e-32 at the 12 th epoch of training.…”
Section: Resultsmentioning
confidence: 99%
“…The GA algorithm can improve the BPNN's slow convergence, which easily falls into the local optima and other issues [25][29]. The optimization goals were the optimization of network weights, the network structure, and learning rules [26][30]. In this paper, the weights and thresholds were optimized by a genetic algorithm.…”
Section: Methodsmentioning
confidence: 99%